Positive electrode for non-aqueous electrolyte storage element and non-aqueous electrolyte storage element
The positive electrode in nonaqueous electrolyte storage devices, featuring a high porosity active material layer with specific carbon black content and pore volume characteristics, effectively reduces AC resistance while maintaining handling properties.
Patent Information
- Application Number
- JP2020194752
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-11-24
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2040-11-24
AI Technical Summary
In nonaqueous electrolyte storage devices, reducing the porosity of the positive electrode active material layer to minimize AC resistance is challenging due to the risk of cracking and deterioration in handling properties, while increasing porosity leads to higher AC resistance.
A positive electrode with a high porosity (40% or more) active material layer containing carbon black, where the carbon black content is 6% or less, and the maximum Log differential pore volume in the pore diameter range of 0.04 μm to 0.1 μm is greater than 0.24 cm^3/g, facilitating a good conductive network.
This configuration reduces the AC resistance of the nonaqueous electrolyte storage device even when the positive electrode active material layer has a high porosity, without compromising the handling properties of the electrode mixture paste.
Smart Images

Figure 0007665962000002 
Figure 0007665962000003 
Figure 0007665962000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a positive electrode for a nonaqueous electrolyte storage element and a nonaqueous electrolyte storage element. [Background technology]
[0002] Non-aqueous electrolyte secondary batteries, such as lithium ion secondary batteries, are widely used in electronic devices such as personal computers and communication terminals, automobiles, etc., due to their high energy density. The non-aqueous electrolyte secondary batteries generally have a pair of electrodes electrically isolated by a separator and a non-aqueous electrolyte interposed between the electrodes, and are configured to charge and discharge by transferring ions between the electrodes. In addition, capacitors such as lithium ion capacitors and electric double layer capacitors are also widely used as storage elements other than non-aqueous electrolyte secondary batteries.
[0003] In the prior art, a positive electrode layer is provided that contains a lithium composite metal oxide containing nickel and a vinylidene fluoride-based fluororubber, and the porosity of the positive electrode layer measured by mercury intrusion porosimetry is 20% to 50%, and the amount of pores having a diameter of 0.1 μm to 3 μm measured by mercury intrusion porosimetry is 10 mm 3 / g~150mm 3 / g, a nonaqueous electrolyte secondary battery has been proposed that has high energy density and excellent large current discharge characteristics and charge / discharge cycle characteristics (see Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 10-255763 Summary of the Invention [Problem to be solved by the invention]
[0005] In general, by reducing the porosity of the positive electrode active material layer of a non-aqueous electrolyte storage element, a conductive network is easily formed, and the current collection resistance tends to be reduced. However, in order to reduce the porosity of the positive electrode active material layer, multiple pressings or pressing under high linear pressure are required. If such pressing is performed on the positive electrode active material layer, the positive electrode active material may crack, and the life performance of the non-aqueous electrolyte storage element may be reduced. On the other hand, if the porosity of the positive electrode active material layer is increased, the current collection resistance of the non-aqueous electrolyte storage element may increase. In order to suppress the increase in the current collection resistance, if the content of the conductive agent in the positive electrode active material layer is increased, the handling property of the positive electrode mixture paste is likely to decrease.
[0006] The present invention has been made in light of the above circumstances, and has an object to provide a positive electrode for a nonaqueous electrolyte storage element that can reduce the AC resistance of the nonaqueous electrolyte storage element even when the positive electrode active material layer has a high porosity. [Means for solving the problem]
[0007] A positive electrode for a non-aqueous electrolyte storage element according to one aspect of the present invention includes a positive electrode active material layer containing a positive electrode active material and carbon black, the positive electrode active material layer having a porosity of 40% or more, a content of the carbon black in the positive electrode active material layer of 6 mass % or less, and a maximum value of the Log differential pore volume in the positive electrode active material layer for pore diameters in the range of 0.04 μm or more and 0.1 μm or less of 0.24 cm 3 / g or more. Effect of the Invention
[0008] A positive electrode for a non-aqueous electrolyte storage element according to one aspect of the present invention can reduce the AC resistance of the non-aqueous electrolyte storage element even when the positive electrode active material layer has a high porosity. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a perspective view showing one embodiment of a nonaqueous electrolyte electricity storage element. [Diagram 2]FIG. 2 is a schematic diagram showing one embodiment of an electricity storage device formed by assembling a plurality of nonaqueous electrolyte electricity storage elements. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] First, an overview of the positive electrode for a nonaqueous electrolyte storage element and the nonaqueous electrolyte storage element disclosed in this specification will be described.
[0011] A positive electrode for a non-aqueous electrolyte storage element according to one aspect of the present invention includes a positive electrode active material layer containing a positive electrode active material and carbon black, the positive electrode active material layer having a porosity of 40% or more, a content of the carbon black in the positive electrode active material layer of 6 mass % or less, and a maximum value of the Log differential pore volume in the positive electrode active material layer for pore diameters in the range of 0.04 μm or more and 0.1 μm or less of 0.24 cm 3 / g or more.
[0012] In the positive electrode for a nonaqueous electrolyte storage element, the positive electrode active material layer contains carbon black as a conductive agent, and the maximum value of the Log differential pore volume in a specific range of pore diameters is equal to or greater than the above lower limit, so that even when the porosity of the positive electrode active material layer is high, the AC resistance of the nonaqueous electrolyte storage element can be reduced. Although the reason for this is unclear, the following reason is presumed. In general, when the porosity of the positive electrode active material layer is high, a conductive network is difficult to form, and the resistance is likely to be high. Furthermore, when the carbon black contained in the positive electrode active material layer is not sufficiently dispersed, the pore volume derived from the carbon black is thought to decrease as the lumpy carbon black is compressed during pressing. In addition, when the structure of the carbon black is cut by applying a strong shear force during kneading the positive electrode mixture paste, the pore volume derived from the carbon black is thought to decrease. From the above, it is presumed that when the carbon black forms a good conductive network, the pore volume is likely to be high. In the positive electrode for a nonaqueous electrolyte storage element, the specific content of carbon black is contained, and the maximum value of the Log differential pore volume is equal to or greater than the lower limit, so that the carbon black forms a good conductive network, and the AC resistance of the nonaqueous electrolyte storage element can be reduced even when the porosity of the positive electrode active material layer is high. Here, the "AC resistance" refers to the AC resistance at 1 kHz, and the current collection resistance of the nonaqueous electrolyte storage element can be evaluated by the AC resistance at 1 kHz.
[0013] The porosity of the positive electrode active material layer refers to a value calculated by the following formula from the true density of the positive electrode active material layer calculated from the true density and content of each component constituting the positive electrode active material layer and the apparent density of the positive electrode active material layer. Porosity (%) = 100 - (apparent density / true density) x 100 Apparent density = coating weight of positive electrode active material layer / thickness of positive electrode active material layer "Log differential pore volume (dV / d(logD))" indicates the relationship between the size of the pores in the sample and their volume, and refers to the value obtained by dividing the differential pore volume dV, which is the increase in pore volume between the measurement points of the pore diameter, by the logarithmic difference value d(logD) of the pore diameter.
[0014] The carbon black preferably has an aromatic surface functional group, which makes it easier to adjust the pore size of the positive electrode for a non-aqueous electrolyte storage element.
[0015] A nonaqueous electrolyte storage element according to one aspect of the present invention includes the positive electrode. By including the positive electrode in the nonaqueous electrolyte storage element, the AC resistance of the nonaqueous electrolyte storage element can be reduced even when the positive electrode active material layer has a high porosity.
[0016] The configuration of a positive electrode for a nonaqueous electrolyte storage element according to one embodiment of the present invention and the configuration of a nonaqueous electrolyte storage element will be described in detail. Note that the names of the components (components) used in each embodiment may differ from the names of the components (components) used in the background art.
[0017] <Positive electrode for non-aqueous electrolyte storage element> The positive electrode has a positive electrode substrate and a positive electrode active material layer disposed on the positive electrode substrate directly or via an intermediate layer.
[0018] (Positive electrode substrate) The positive electrode substrate is conductive. Whether or not it has "conductivity" is determined by whether the volume resistivity measured in accordance with JIS-H-0505 (1975) is 10 7 The threshold value is Ω·cm. The material of the positive electrode substrate is a metal such as aluminum, titanium, tantalum, stainless steel, or an alloy thereof. Among these, aluminum or an aluminum alloy is preferred from the viewpoints of potential resistance, high conductivity, and cost. The positive electrode substrate may be a foil, a vapor deposition film, a mesh, a porous material, etc., and a foil is preferred from the viewpoint of cost. Therefore, aluminum foil or an aluminum alloy foil is preferred as the positive electrode substrate. Examples of aluminum or an aluminum alloy include A1085, A3003, A1N30, etc., as specified in JIS-H-4000 (2014) or JIS-H4160 (2006).
[0019] The average thickness of the positive electrode substrate is preferably 3 μm to 50 μm, more preferably 5 μm to 40 μm, even more preferably 8 μm to 30 μm, and particularly preferably 10 μm to 25 μm. By setting the average thickness of the positive electrode substrate within the above range, it is possible to increase the strength of the positive electrode substrate and to increase the energy density per volume of the secondary battery.
[0020] (Middle class) The intermediate layer is a layer disposed between the positive electrode substrate and the positive electrode active material layer. The intermediate layer contains a conductive agent such as carbon particles to reduce the contact resistance between the positive electrode substrate and the positive electrode active material layer. The configuration of the intermediate layer is not particularly limited, and may contain, for example, a binder and a conductive agent.
[0021] (Cathode active material layer) The positive electrode active material layer contains a positive electrode active material and carbon black, and may further contain optional components such as a binder, a thickener, and a filler, as necessary.
[0022] The positive electrode active material can be appropriately selected from known positive electrode active materials. As the positive electrode active material for a lithium ion secondary battery, a material capable of absorbing and releasing lithium ions is usually used. As the positive electrode active material, for example, α-NaFeO 2 Lithium transition metal composite oxides having a crystalline structure, lithium transition metal composite oxides having a spinel crystalline structure, polyanion compounds, chalcogen compounds, sulfur, etc. 2 As an example of a lithium transition metal composite oxide having a crystalline structure, Li[Li x Ni (1-x) ]O 2 (0≦x<0.5), Li[Li x Ni γ Co (1-x-γ) ]O 2 (0≦x<0.5, 0<γ<1), Li[Li x Co (1-x) ]O 2 (0≦x<0.5), Li[Li x Ni γ Mn (1-x-γ) ]O 2(0≦x<0.5, 0<γ<1), Li[Li x Ni γ Mn β Co (1-x-γ-β) ]O 2 (0≦x<0.5, 0<γ, 0<β, 0.5<γ+β<1), Li[Li x Ni γ Co β Al (1-x-γ-β) ]O 2 (0≦x<0.5, 0<γ, 0<β, 0.5<γ+β<1). Lithium transition metal composite oxides with spinel crystal structure include Li x Mn 2 O 4 , Li x Ni γ Mn (2-γ) O 4 Examples of polyanion compounds include LiFePO 4 , LiMnPO 4 , LiNiPO 4 , LiCoPO 4 ,Li 3 V 2 (PO 4 ) 3 , Li 2 MnSiO 4 , Li 2 CoPO 4 Examples of the chalcogen compound include titanium disulfide, molybdenum disulfide, and molybdenum dioxide. The atoms or polyanions in these materials may be partially substituted with atoms or anion species of other elements. The surfaces of these materials may be coated with other materials. In the positive electrode active material layer, one of these materials may be used alone, or two or more of them may be used in combination.
[0023] The positive electrode active material is usually a particle (powder). The average particle size of the positive electrode active material is preferably, for example, 0.1 μm or more and 20 μm or less. By setting the average particle size of the positive electrode active material to the above lower limit or more, the positive electrode active material can be easily manufactured or handled. By setting the average particle size of the positive electrode active material to the above upper limit or less, the electronic conductivity of the positive electrode active material layer is improved. In addition, when a composite of the positive electrode active material and another material is used, the average particle size of the composite is taken as the average particle size of the positive electrode active material. The "average particle size" means a value at which the volume-based cumulative distribution calculated in accordance with JIS-Z-8819-2 (2001) is 50% based on the particle size distribution measured by a laser diffraction / scattering method for a diluted solution obtained by diluting particles with a solvent in accordance with JIS-Z-8825 (2013).
[0024] In order to obtain powder with a predetermined particle size, a pulverizer, a classifier, etc. are used. Examples of the pulverization method include a method using a mortar, a ball mill, a sand mill, a vibration ball mill, a planetary ball mill, a jet mill, a counter jet mill, a swirling airflow type jet mill, or a sieve. During pulverization, wet pulverization in the presence of water or an organic solvent such as hexane can also be used. As a classification method, a sieve, an air classifier, etc. are used as necessary for both the dry and wet methods.
[0025] The content of the positive electrode active material in the positive electrode active material layer is preferably 50% by mass to 99% by mass, more preferably 70% by mass to 98% by mass, and even more preferably 80% by mass to 95% by mass. By setting the content of the positive electrode active material in the above range, both high energy density and manufacturability of the positive electrode active material layer can be achieved.
[0026] As described above, the positive electrode active material layer contains carbon black as a conductive agent. Examples of carbon black include furnace black, acetylene black, and ketjen black. Among these, acetylene black is preferable. In addition, one type of carbon black or two or more types of carbon black may be used in combination.
[0027] The carbon black preferably has an aromatic surface functional group. When the carbon black has an aromatic surface functional group, the pore size of the positive electrode for the nonaqueous electrolyte storage element can be easily adjusted. Examples of the aromatic surface functional group include a phenyl group and a tolyl group.
[0028] The upper limit of the carbon black content in the positive electrode active material layer is 6 mass%, preferably 5 mass%, and more preferably 4.5 mass%. Meanwhile, the lower limit of the carbon black content is preferably 2 mass%, and more preferably 1 mass%. By having the carbon black content in the positive electrode active material layer within the above range, sufficient conductivity of the nonaqueous electrolyte storage element can be ensured without deteriorating the handleability of the positive electrode mixture paste.
[0029] The positive electrode active material layer may contain other conductive agents other than the carbon black. The other conductive agents are not particularly limited as long as they are conductive materials. Examples of such conductive agents include carbonaceous materials, metals, conductive ceramics, and the like. Examples of carbonaceous materials include graphite, non-graphitic carbon, graphene-based carbon, and the like. Examples of non-graphitic carbon include carbon nanofibers and pitch-based carbon fibers. Examples of graphene-based carbon include graphene and fullerene. Examples of the shape of the conductive agent include powder and fiber. As the other conductive agent, one of these materials may be used alone, or two or more of them may be mixed and used. These materials may also be used in a composite form. The content of the other conductive agent other than the carbon black in the positive electrode active material layer is preferably 2% by mass or less, and may be 0% by mass.
[0030] Examples of binders include thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, polyacrylic, polyimide, etc.; elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, etc.; polysaccharide polymers, etc.
[0031] The binder content in the positive electrode active material layer is preferably from 1% by mass to 10% by mass, and more preferably from 2% by mass to 9% by mass. By setting the binder content in the above range, the active material can be stably held.
[0032] Examples of the thickener include polysaccharide polymers such as carboxymethyl cellulose (CMC), methyl cellulose, etc. When the thickener has a functional group that reacts with lithium or the like, this functional group may be deactivated in advance by methylation or the like.
[0033] The filler is not particularly limited. Examples of the filler include polyolefins such as polypropylene and polyethylene, inorganic oxides such as silicon dioxide, alumina, titanium dioxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicates, hydroxides such as magnesium hydroxide, calcium hydroxide, and aluminum hydroxide, carbonates such as calcium carbonate, poorly soluble ion crystals such as calcium fluoride, barium fluoride, and barium sulfate, nitrides such as aluminum nitride and silicon nitride, and mineral resource-derived substances such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, or artificial products thereof.
[0034] The positive electrode active material layer may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, and I, typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, and Ba, and transition metallic elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Nb, and W as components other than the positive electrode active material, conductive agent, binder, thickener, and filler.
[0035] The lower limit of the maximum value of the Log differential pore volume in the pore diameter range of 0.04 μm or more and 0.1 μm or less of the positive electrode active material layer is 0.24 cm 3 / g, 0.3 cm 3When the maximum value of the Log differential pore volume is equal to or greater than the lower limit, a conductive network is easily formed, and even when the porosity of the positive electrode active material layer is high, the AC resistance of the nonaqueous electrolyte storage element can be reduced. On the other hand, the upper limit of the maximum value of the Log differential pore volume is preferably 0.40 cm 3 / g. The maximum value of the Log differential pore volume is preferably 0.40 cm 3 / g or less, the pore volume does not become too large, so that peeling of the electrode plate due to a decrease in the adhesion of the positive electrode active material layer can be suppressed. The Log differential pore volume of the positive electrode active material layer can be adjusted by the particle size and specific surface area of the positive electrode active material, the composition and thickness of the positive electrode active material layer, whether or not the positive electrode active material layer is pressed during production, and the strength of the linear pressure of the press.
[0036] The Log differential pore volume of the positive electrode active material layer in the pore diameter range of 0.04 μm or more and 0.1 μm or less is measured by mercury intrusion porosimetry according to the following procedure. The pore volume distribution is measured by mercury intrusion porosimetry using AutoPore9400 (Micromeritics). The contact angle of mercury is set to 130° and the surface tension to 484 dynes / cm. The pore diameter range to be measured is from 0.006 μm to 20 μm. The pore diameter is plotted on the horizontal axis and the pore volume on the vertical axis to obtain a cumulative pore volume curve. Next, the differential volume dV between the measurement points is divided by the logarithmic differential value d(logD) of the pore diameter to obtain a value, and the Log differential pore volume curve is obtained by plotting this value against the average pore diameter of each section. The "maximum value of the Log differential pore volume in the pore diameter range of 0.04 μm to 0.1 μm" is the maximum value of the Log differential pore volume in the pore diameter range of 0.04 μm to 0.1 μm in the Log differential pore volume curve. The sample of the positive electrode active material layer to be used for the measurement of the pore volume distribution is prepared by the following method. The nonaqueous electrolyte storage element is discharged at a current of 0.1 C to the discharge end voltage during normal use to leave it in a discharged state. Here, "normal use" refers to a case where the nonaqueous electrolyte storage element is used under the discharge conditions recommended or specified for the nonaqueous electrolyte storage element. The nonaqueous electrolyte storage element in the discharged state is disassembled, the positive electrode is removed and used as the working electrode, and a single-electrode battery is assembled using metallic Li as the counter electrode. When the positive electrode potential reaches 3.0 V (vs. Li / Li) at a current of 0.1 C, + ) The single-electrode battery is disassembled, and the removed positive electrode is thoroughly washed with dimethyl carbonate and then dried under reduced pressure at room temperature. After drying, the positive electrode is cut to a specified size (e.g., 2 x 2 cm) and used as a sample for measuring pore volume distribution. The operations from disassembling the battery to cutting out the sample for measuring pore volume distribution are carried out in a dry air atmosphere with a dew point of -40°C or less.
[0037] The lower limit of the porosity of the positive electrode active material layer is 40%, preferably 44%. When the porosity of the positive electrode active material layer is equal to or higher than the lower limit, multiple pressing or pressing under high linear pressure is not required, and cracking of the positive electrode active material can be suppressed. On the other hand, the upper limit of the porosity of the positive electrode active material layer is preferably, for example, 50%. When the porosity of the positive electrode active material layer is equal to or lower than the upper limit, the capacity density per volume of the positive electrode active material layer can be increased. The porosity of the positive electrode active material layer can be adjusted by the strength of the linear pressure of the press when forming the positive electrode active material layer.
[0038] According to this positive electrode for a nonaqueous electrolyte storage element, even when the positive electrode active material layer has a high porosity, the AC resistance of the nonaqueous electrolyte storage element can be reduced.
[0039] <Non-aqueous electrolyte electricity storage element> A nonaqueous electrolyte storage element (hereinafter, also simply referred to as "storage element") according to one embodiment of the present invention includes an electrode assembly having a positive electrode, a negative electrode, and a separator, a nonaqueous electrolyte, and a container that contains the electrode assembly and the nonaqueous electrolyte. The electrode assembly is usually of a laminated type in which a plurality of positive electrodes and a plurality of negative electrodes are laminated with a separator interposed therebetween, or of a wound type in which a positive electrode and a negative electrode are laminated with a separator interposed therebetween and wound. The nonaqueous electrolyte exists in a state in which it is impregnated in the positive electrode, the negative electrode, and the separator. As an example of a nonaqueous electrolyte storage element, a nonaqueous electrolyte secondary battery (hereinafter, also simply referred to as "secondary battery") will be described.
[0040] [Positive electrode] The positive electrode included in the nonaqueous electrolyte storage element is as described above.
[0041] [Negative electrode] The negative electrode has a negative electrode substrate and a negative electrode active material layer disposed on the negative electrode substrate directly or via an intermediate layer. The configuration of the intermediate layer is not particularly limited and can be selected from the configurations exemplified for the positive electrode.
[0042] (Negative electrode substrate) The negative electrode substrate has electrical conductivity. Metals such as copper, nickel, stainless steel, nickel-plated steel, and aluminum, or alloys thereof, carbonaceous materials, etc. are used as the material of the negative electrode substrate. Among these, copper or copper alloys are preferred. Examples of the negative electrode substrate include foils, vapor deposition films, meshes, and porous materials, and foils are preferred from the viewpoint of cost. Therefore, copper foil or copper alloy foil is preferred as the negative electrode substrate. Examples of copper foil include rolled copper foil and electrolytic copper foil.
[0043] The average thickness of the negative electrode substrate is preferably 2 μm to 35 μm, more preferably 3 μm to 30 μm, further preferably 4 μm to 25 μm, and particularly preferably 5 μm to 20 μm. By setting the average thickness of the negative electrode substrate within the above range, it is possible to increase the strength of the negative electrode substrate and to increase the energy density per volume of the secondary battery.
[0044] (Negative electrode active material layer) The negative electrode active material layer contains a negative electrode active material. The negative electrode active material layer contains optional components such as a conductive agent, a binder, a thickener, a filler, etc., as necessary. The optional components such as a conductive agent, a binder, a thickener, a filler, etc. can be selected from the materials exemplified for the positive electrode above.
[0045] The negative electrode active material layer may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, and I, typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, and Ba, and transition metallic elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Ta, Hf, Nb, and W as components other than the negative electrode active material, conductive agent, binder, thickener, and filler.
[0046] The negative electrode active material can be appropriately selected from known negative electrode active materials. A material capable of absorbing and releasing lithium ions is usually used as the negative electrode active material for lithium ion secondary batteries. Examples of the negative electrode active material include metal Li; metals or semimetals such as Si and Sn; metal oxides or semimetal oxides such as Si oxide, Ti oxide, and Sn oxide; Li 4 Ti 5 O 12 , LiTiO2、 TiNb 2 O 7 Examples of the material include titanium-containing oxides such as titanium oxide, polyphosphate compounds, silicon carbide, and carbon materials such as graphite and non-graphitic carbon (easily graphitized carbon or non-graphitizable carbon). Among these materials, graphite and non-graphitic carbon are preferred. In the negative electrode active material layer, one of these materials may be used alone, or two or more of them may be used in combination.
[0047] "Graphite" refers to graphite that has an average lattice spacing (d 002 ) is 0.33 nm or more and less than 0.34 nm. Examples of graphite include natural graphite and artificial graphite. Artificial graphite is preferred from the viewpoint of availability of materials with stable physical properties.
[0048] "Non-graphitic carbon" refers to carbon that has an average lattice spacing (d 002 ) is 0.34 nm or more and 0.42 nm or less. Examples of non-graphitizable carbon include non-graphitizable carbon and graphitizable carbon. Examples of non-graphitizable carbon include resin-derived materials, petroleum pitch or petroleum pitch-derived materials, petroleum coke or petroleum coke-derived materials, plant-derived materials, and alcohol-derived materials.
[0049] Here, the "discharged state" refers to a state in which the negative electrode active material carbon material is discharged so that lithium ions that can be absorbed and released during charging and discharging are sufficiently released. For example, in a single-electrode battery using a negative electrode containing a carbon material as a negative electrode active material as a working electrode and metallic Li as a counter electrode, the state is one in which the open circuit voltage is 0.7 V or more.
[0050] "Non-graphitizable carbon" means the above d 002 This refers to carbon materials with a particle size of 0.36 nm or more and 0.42 nm or less.
[0051] "Graphitizable carbon" means the above d 002This refers to carbon materials with a particle size of 0.34 nm or more and less than 0.36 nm.
[0052] The negative electrode active material is usually a particle (powder). The average particle size of the negative electrode active material can be, for example, 1 nm or more and 100 μm or less. When the negative electrode active material is a carbon material, a titanium-containing oxide, or a polyphosphate compound, the average particle size may be 1 μm or more and 100 μm or less. When the negative electrode active material is Si, Sn, Si oxide, Sn oxide, or the like, the average particle size may be 1 nm or more and 1 μm or less. By setting the average particle size of the negative electrode active material to the above lower limit or more, the negative electrode active material can be easily manufactured or handled. By setting the average particle size of the negative electrode active material to the above upper limit or less, the electronic conductivity of the active material layer is improved. In order to obtain powder with a predetermined particle size, a pulverizer, a classifier, or the like is used. The pulverization method and the powder classification method can be selected from, for example, the methods exemplified for the positive electrode. When the negative electrode active material is a metal such as metallic Li, the negative electrode active material may be in the form of a foil.
[0053] The content of the negative electrode active material in the negative electrode active material layer is preferably 60% by mass to 99% by mass, more preferably 90% by mass to 98% by mass. By setting the content of the negative electrode active material in the above range, both high energy density and manufacturability of the negative electrode active material layer can be achieved.
[0054] [Separator] The separator can be appropriately selected from known separators. For example, a separator consisting of only a substrate layer, a separator in which a heat-resistant layer containing heat-resistant particles and a binder is formed on one or both surfaces of the substrate layer, etc. can be used as the separator. Examples of the shape of the substrate layer of the separator include woven fabric, nonwoven fabric, and porous resin film. Among these shapes, a porous resin film is preferred from the viewpoint of strength, and a nonwoven fabric is preferred from the viewpoint of non-aqueous electrolyte retention. As the material of the substrate layer of the separator, polyolefins such as polyethylene and polypropylene are preferred from the viewpoint of shutdown function, and polyimide and aramid are preferred from the viewpoint of oxidation decomposition resistance. A material obtained by combining these resins may be used as the substrate layer of the separator.
[0055] The heat-resistant particles contained in the heat-resistant layer preferably have a mass loss of 5% or less when heated from room temperature to 500°C under an air atmosphere at 1 atmosphere, and more preferably have a mass loss of 5% or less when heated from room temperature to 800°C. Examples of materials with a mass loss of a predetermined amount or less include inorganic compounds. Examples of inorganic compounds include oxides such as iron oxide, silicon oxide, aluminum oxide, titanium oxide, barium titanate, zirconium oxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicate; nitrides such as aluminum nitride and silicon nitride; carbonates such as calcium carbonate; sulfates such as barium sulfate; sparingly soluble ion crystals such as calcium fluoride and barium fluoride; covalent crystals such as silicon and diamond; mineral resource-derived substances such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, or artificial products thereof. As the inorganic compound, these substances may be used alone or in the form of a complex, or two or more of them may be mixed and used. Among these inorganic compounds, silicon oxide, aluminum oxide, or aluminosilicate is preferred from the viewpoint of the safety of the energy storage element.
[0056] The porosity of the separator is preferably 80% by volume or less from the viewpoint of strength, and is preferably 20% by volume or more from the viewpoint of discharge performance. Here, "porosity" refers to a volume-based value measured with a mercury porosimeter.
[0057] As the separator, a polymer gel composed of a polymer and a non-aqueous electrolyte may be used. Examples of the polymer include polyacrylonitrile, polyethylene oxide, polypropylene oxide, polymethyl methacrylate, polyvinyl acetate, polyvinylpyrrolidone, and polyvinylidene fluoride. The use of the polymer gel has an effect of suppressing leakage. As the separator, the above-mentioned porous resin film or nonwoven fabric may be used in combination with the polymer gel.
[0058] [Non-aqueous electrolyte] The nonaqueous electrolyte may be appropriately selected from known nonaqueous electrolytes. The nonaqueous electrolyte may be a nonaqueous electrolyte solution. The nonaqueous electrolyte solution includes a nonaqueous solvent and an electrolyte salt dissolved in the nonaqueous solvent.
[0059] The non-aqueous solvent can be appropriately selected from known non-aqueous solvents. Examples of the non-aqueous solvent include cyclic carbonates, chain carbonates, carboxylates, phosphates, sulfonates, ethers, amides, and nitriles. As the non-aqueous solvent, those in which some of the hydrogen atoms contained in these compounds are substituted with halogens may be used.
[0060] Examples of cyclic carbonates include ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinylene carbonate (VC), vinylethylene carbonate (VEC), chloroethylene carbonate, fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), styrene carbonate, 1-phenylvinylene carbonate, 1,2-diphenylvinylene carbonate, etc. Among these, EC is preferred.
[0061] Examples of the chain carbonate include diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diphenyl carbonate, trifluoroethyl methyl carbonate, bis(trifluoroethyl) carbonate, etc. Among these, EMC is preferable.
[0062] As the non-aqueous solvent, it is preferable to use a cyclic carbonate or a chain carbonate, and it is more preferable to use a combination of a cyclic carbonate and a chain carbonate. By using a cyclic carbonate, it is possible to promote dissociation of the electrolyte salt and improve the ionic conductivity of the non-aqueous electrolyte. By using a chain carbonate, it is possible to keep the viscosity of the non-aqueous electrolyte low. When using a cyclic carbonate and a chain carbonate in combination, it is preferable that the volume ratio of the cyclic carbonate to the chain carbonate (cyclic carbonate:chain carbonate) is, for example, in the range of 5:95 to 50:50.
[0063] The electrolyte salt can be appropriately selected from known electrolyte salts. Examples of the electrolyte salt include lithium salts, sodium salts, potassium salts, magnesium salts, onium salts, etc. Among these, lithium salts are preferred.
[0064] The lithium salt is LiPF 6 , LiPO 2 F 2 , LiBF 4 , LiClO 4 , LiN(SO 2 F) 2 inorganic lithium salts such as lithium oxalate (LiBOB), lithium difluorooxalate (LiFOB), lithium bis(oxalate) difluorophosphate (LiFOP), and other lithium oxalates; LiSO 3 CF 3 , LiN(SO 2 CF 3 ) 2 , LiN(SO 2 C 2 F 5 ) 2 , LiN(SO 2 CF 3 )(SO 2 C 4 F 9 ), LiC(SO 2 CF 3 ) 3 , LiC(SO 2 C 2 F 5 )3 Among these, inorganic lithium salts are preferred, and LiPF 6 is more preferred.
[0065] The electrolyte salt content in the non-aqueous electrolyte is 0.1 mol / dm at 20°C and 1 atmosphere. 3 More than 2.5mol / dm 3 It is preferable that the value is 0.3 mol / dm or less. 3 More than 2.0mol / dm 3 More preferably, it is 0.5 mol / dm or less. 3 More than 1.7mol / dm 3 More preferably, it is 0.7 mol / dm or less. 3 More than 1.5mol / dm 3 By setting the content of the electrolyte salt within the above range, the ionic conductivity of the nonaqueous electrolyte can be increased.
[0066] The non-aqueous electrolyte may contain additives in addition to the non-aqueous solvent and the electrolyte salt. Examples of additives include halogenated carbonates such as fluoroethylene carbonate (FEC) and difluoroethylene carbonate (DFEC); oxalates such as lithium bis(oxalate)borate (LiBOB), lithium difluorooxalateborate (LiFOB), and lithium bis(oxalate)difluorophosphate (LiFOP); imide salts such as lithium bis(fluorosulfonyl)imide (LiFSI); biphenyl, alkylbiphenyl, terphenyl, partially hydrogenated terphenyl, cyclohexyl, and the like. Aromatic compounds such as benzene, t-butylbenzene, t-amylbenzene, diphenyl ether, and dibenzofuran; partial halides of the above aromatic compounds such as 2-fluorobiphenyl, o-cyclohexylfluorobenzene, and p-cyclohexylfluorobenzene; halogenated anisole compounds such as 2,4-difluoroanisole, 2,5-difluoroanisole, 2,6-difluoroanisole, and 3,5-difluoroanisole; vinylene carbonate, methylvinylene carbonate, ethylvinylene carbonate, succinic anhydride, Glutaric anhydride, maleic anhydride, citraconic anhydride, glutaconic anhydride, itaconic anhydride, cyclohexanedicarboxylic anhydride; ethylene sulfite, propylene sulfite, dimethyl sulfite, propane sultone, propene sultone, butane sultone, methyl methanesulfonate, busulfan, methyl toluenesulfonate, dimethyl sulfate, ethylene sulfate, sulfolane, dimethyl sulfone, diethyl sulfone, dimethyl sulfoxide, diethyl sulfoxide, tetramethylene sulfoxide, diphenyl sulfide, 4,4'-bis(2,2- dioxo-1,3,2-dioxathiolane), 4-methylsulfonyloxymethyl-2,2-dioxo-1,3,2-dioxathiolane, thioanisole, diphenyl disulfide, dipyridinium disulfide, 1,3-propene sultone, 1,3-propane sultone, 1,4-butane sultone, 1,4-butene sultone, perfluorooctane, tristrimethylsilyl borate, tristrimethylsilyl phosphate, tetrakistrimethylsilyl titanate, lithium monofluorophosphate, lithium difluorophosphate, and the like.These additives may be used alone or in combination of two or more.
[0067] The content of the additive contained in the non-aqueous electrolyte is preferably 0.01% by mass to 10% by mass, more preferably 0.1% by mass to 7% by mass, even more preferably 0.2% by mass to 5% by mass, and particularly preferably 0.3% by mass to 3% by mass. By setting the content of the additive within the above range, it is possible to improve the capacity retention performance or cycle performance after high-temperature storage, and to further improve safety.
[0068] The non-aqueous electrolyte may be a solid electrolyte, or a non-aqueous electrolyte solution and a solid electrolyte may be used in combination.
[0069] The solid electrolyte can be selected from any material that has ionic conductivity such as lithium, sodium, calcium, etc., and is solid at room temperature (e.g., 15° C. to 25° C.). Examples of the solid electrolyte include sulfide solid electrolytes, oxide solid electrolytes, oxynitride solid electrolytes, polymer solid electrolytes, etc.
[0070] As a sulfide solid electrolyte, for example, Li 2 SP 2 S 5 , LiI-Li 2 SP 2 S 5 , Li 10 Ge-P 2 S 12 etc.
[0071] <Specific Configuration of Nonaqueous Electrolyte Energy Storage Element> The shape of the energy storage element of this embodiment is not particularly limited, and examples thereof include a cylindrical battery, a square battery, a flat battery, a coin battery, and a button battery.
[0072] Fig. 1 shows a nonaqueous electrolyte storage element 1 as an example of a prismatic battery. The figure is a see-through view of the inside of the container. An electrode body 2 having a positive electrode and a negative electrode wound with a separator sandwiched therebetween is housed in a prismatic container 3. The positive electrode is electrically connected to a positive electrode terminal 4 via a positive electrode lead 41. The negative electrode is electrically connected to a negative electrode terminal 5 via a negative electrode lead 51.
[0073] [Configuration of the Nonaqueous Electrolyte Electricity Storage Device] The nonaqueous electrolyte storage element of the present embodiment can be mounted as an electricity storage device comprising a plurality of nonaqueous electrolyte storage elements 1 assembled together in an automobile power source such as an electric vehicle (EV), a hybrid electric vehicle (HEV), a plug-in hybrid electric vehicle (PHEV), etc., a power source for electronic devices such as a personal computer or a communication terminal, or a power storage power source, etc. In this case, the technology of the present invention may be applied to at least one nonaqueous electrolyte storage element included in the electricity storage device. 2 shows an example of an electricity storage device 30 in which electricity storage units 20, each of which is an assembly of two or more electrically connected electricity storage elements 1, are further assembled. The electricity storage device 30 may include a bus bar (not shown) that electrically connects two or more nonaqueous electrolyte electricity storage elements 1, a bus bar (not shown) that electrically connects two or more electricity storage units 20, and the like. The electricity storage unit 20 or the electricity storage device 30 may include a status monitoring device (not shown) that monitors the status of the one or more nonaqueous electrolyte electricity storage elements.
[0074] [Method of manufacturing non-aqueous electrolyte storage element] The nonaqueous electrolyte secondary battery (nonaqueous electrolyte storage element) can be manufactured by a known method, except for using the positive electrode as the positive electrode. The manufacturing method includes, for example, preparing an electrode body, preparing a nonaqueous electrolyte, and housing the electrode body and the nonaqueous electrolyte in a container. The preparation of the electrode body includes preparing a positive electrode and a negative electrode, and forming the electrode body by stacking or rolling the positive electrode and the negative electrode with a separator interposed therebetween.
[0075] The method of housing the non-aqueous electrolyte in the container can be appropriately selected from known methods. For example, when a non-aqueous electrolyte solution is used as the non-aqueous electrolyte, the non-aqueous electrolyte solution may be injected through an injection port formed in the container, and then the injection port may be sealed.
[0076] According to the nonaqueous electrolyte storage element, by including the positive electrode, the AC resistance of the nonaqueous electrolyte storage element can be reduced even when the positive electrode active material layer has a high porosity.
[0077] <Other embodiments> The nonaqueous electrolyte storage element of the present invention is not limited to the above-described embodiment, and various modifications may be made without departing from the scope of the present invention. For example, the configuration of one embodiment may be added to the configuration of another embodiment, and part of the configuration of one embodiment may be replaced with the configuration of another embodiment or a well-known technique. Furthermore, part of the configuration of one embodiment may be deleted. Also, a well-known technique may be added to the configuration of one embodiment.
[0078] In the above embodiment, the nonaqueous electrolyte storage element is used as a chargeable and dischargeable nonaqueous electrolyte secondary battery (e.g., a lithium ion secondary battery), but the type, shape, size, capacity, etc. of the nonaqueous electrolyte storage element are arbitrary. The present invention can also be applied to various secondary batteries, electric double layer capacitors, lithium ion capacitors, and other capacitors.
[0079] In the above embodiment, the electrode assembly in which the positive electrode and the negative electrode are stacked with a separator interposed therebetween has been described, but the electrode assembly may not include a separator. For example, the positive electrode and the negative electrode may be in direct contact with each other in a state in which a non-conductive layer is formed on the active material layer of the positive electrode or the negative electrode. EXAMPLES
[0080] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.
[0081] [Examples 1 to 5 and Comparative Examples 1 to 3] (Preparation of positive electrode) The positive electrode active material is LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 A lithium transition metal composite oxide represented by (NCM111) was used. Carbon black was used as the conductive agent in a content (mass%) shown in Table 1. In Examples 1 to 4, carbon black having an aromatic surface functional group was used, and in Example 5 and Comparative Examples 1 to 3, carbon black having no functional group was used. Polyvinylidene fluoride was used as the binder. N-methylpyrrolidone (NMP) was used as the dispersion medium, and the binder was mixed so that the solid content content of the positive electrode active material layer was 2 mass%, and the total solid content content of the positive electrode active material and the conductive agent shown in Table 1 was the remainder, to obtain a positive electrode mixture paste. Next, the positive electrode mixture paste was applied to one side of the positive electrode active material in an amount of 1.0 g / 100 cm. 2 The positive electrode was obtained by applying the mixture to both sides of an aluminum foil as a positive electrode substrate, drying and pressing the mixture to form a positive electrode active material layer having the porosity shown in Table 1. The porosity of the positive electrode active material layer was calculated by the method described above.
[0082] (Preparation of negative electrode) Graphite was used as the negative active material, styrene-butadiene rubber (SBR) as the binder, and carboxymethyl cellulose (CMC) as the thickener. The negative active material, binder, and thickener were mixed in a mass ratio of 98:1:1, and an appropriate amount of water was added to the mixture to adjust the viscosity, to prepare a negative electrode mixture paste. This negative electrode mixture paste was applied to one side of the negative active material in an amount of 0.6 g / 100 cm. 2 The mixture was applied to both sides of a copper foil serving as a negative electrode substrate, and then dried and pressed to obtain a negative electrode.
[0083] (Preparation of non-aqueous electrolyte) A mixed solvent of EC, DMC, and EMC in a volume ratio of 30:35:35 was added to the LiPF 6 to 1.2 mol / dm 3 A non-aqueous electrolyte was prepared by dissolving the aqueous solution in the above-mentioned solution at a concentration of 1:1.
[0084] (Preparation of non-aqueous electrolyte storage element) The separator used was a substrate layer made of a polyolefin microporous membrane with an inorganic particle layer containing alumina formed on one side thereof. The positive electrode and the negative electrode were laminated with the separator interposed therebetween so that the inorganic particle layer and the positive electrode faced each other, and then wound to prepare a wound electrode body. The electrode body was placed in an aluminum square container, the nonaqueous electrolyte was poured into the container, and the container was sealed.
[0085] (Initial charge / discharge) Each of the nonaqueous electrolyte storage elements was charged at a constant current of 0.2 C to 4.1 V at 25° C., and then charged at a constant voltage of 4.1 V. The charge was terminated when the total charge time reached 7 hours. After a 10-minute pause after charging, the element was discharged at a constant current of 0.2 C to 2.5 V at 25° C. A 10-minute pause was then provided after discharging. The above cycle was repeated twice.
[0086] (Measurement of Log Differential Pore Volume) For each nonaqueous electrolyte storage element after the initial charge and discharge, the Log differential pore volume distribution of the positive electrode active material layer was measured by the method described above, and the maximum value of the Log differential pore volume in the pore diameter range of 0.04 μm to 0.1 μm was calculated. The results are shown in Table 1.
[0087] [evaluation] (AC resistance measurement) The initial alternating current resistance (ACR) at 1 kHz was determined for each nonaqueous electrolyte storage element after the above initial charge and discharge. The ACR of each nonaqueous electrolyte storage element is shown in Table 1 relative to the ACR of the nonaqueous electrolyte storage element of Comparative Example 1 (100%).
[0088] [Table 1]
[0089] As shown in Table 1 above, the carbon black content in the positive electrode active material layer is 6 mass % or less, and the maximum value of the Log differential pore volume in the pore diameter range of 0.04 μm or more and 0.1 μm or less in the positive electrode active material layer is 0.24 cm 3 It can be seen that in Examples 1 to 5, in which the porosity of the positive electrode active material layer is as high as 40% or more, the AC resistance of the nonaqueous electrolyte storage element can be reduced. On the other hand, the maximum value of the Log differential pore volume in the pore diameter range of 0.04 μm or more and 0.1 μm or less of the positive electrode active material layer is 0.24 cm 3 In Comparative Examples 1 to 3, where the average molecular weight was less than 1 / g, the AC resistance of the nonaqueous electrolyte electricity storage elements was higher than that of Examples 1 to 5. [Explanation of symbols]
[0090] 1. Non-aqueous electrolyte storage element 2 Electrode body 3 containers 4 Positive terminal 41 Positive lead 5 Negative terminal 51 Negative lead 20 Energy Storage Unit 30 Energy storage device
Claims
1. A positive electrode active material layer containing a positive electrode active material and carbon black, The porosity of the positive electrode active material layer is 40% or more and 50% or less, the content of the carbon black in the positive electrode active material layer is 6% by mass or less, The maximum value of the log differential pore volume in the pore diameter range of 0.04 μm or more and 0.1 μm or less of the positive electrode active material layer is 0.24 cm 3 / g or more and 0.40 cm 3 / g or less.
2. 2. The positive electrode for a non-aqueous electrolyte storage element according to claim 1, wherein the carbon black has an aromatic surface functional group.
3. A non-aqueous electrolyte electricity storage element comprising the positive electrode according to claim 1 or 2.
Citation Information
Patent Citations
Nonaqueous electrolyte secondary battery and its manufacture
JP1998255763A
Modified carbon products and uses thereof
JP2007529404A
Method for producing self-dispersible type carbon black
JP2016035019A
Lithium-ion battery manufacturing method and lithium-ion battery
JP2020057523A
Secondary battery
WO2012063370A1